Development of Non-Dissolved Aquatic Plant Absorbent Cubes - Kumaran, Rajaletchumi; Fatimah Binti Mohamed Yusop; Nuramidah Binti Hamidon; Hilmi Bin Kosnin (Progress in Engineering Application and Technology, 2025)
Aquatic plants play an important role in water treatment by balancing the biological and improve the overall health of aquatic ecosystem. In this study, the aquatic plant Limnocharis Flava was found at area Bukit Gambir with excessive growth use to make a cube with a suitable binder. Aquatic plants used in water treatment as absorbent to absorb heavy metal in powdered form which cannot be remove once it put in the water bodies. This study aims to determine the optimum ratio of aquatic plants material to binder, evaluate the durability of the absorbent cubes in water, and assess their nutrient absorption efficiency. This study involves collecting aquatic plants from the Bukit Gambir earth drain, powdered it and combined them with guar gum to make the cube absorbent. The cube absorbent undergo immersion testing to assess the physical condition and followed by phosphorus content testing in the drain water. According to the findings, the most resilient absorbent cube, which could withstand up to four days in water, was created by combining 30 grams of Lymnocharis flava with 3 grams of guar gum. Additionally, the absorbent cubes’ performance study showed that the water’s phosphorus levels significantly decreased with time. After four days of immersion, the greatest reduction of 18.43% was seen, demonstrating how well the absorbent improved the quality of the water. The cube’s ability to absorb extra nutrients was demonstrated via immersion tests that assessed their performance in water. After extended exposure to water, the absorbent cubes retained their structural integrity and lowered the phosphorus.